IMPLANTATION OF THE MICRA ELECTRODELESS MINIATURE ARTIFICIAL HEART GUIDE: EXPERIENCE AND CASE SERIES - Kostić, Tomislav; Perišić, Zoran; Apostolović, Svetlana; Dakić, Sonja; Stanojevic, Dragana; Božinović, Nenad; Maričić, Bojan; Đorđević-Radojković, Danijela; Koraćević, Goran; Cvetković, Predrag; Nikolić, Miroslav; Kostić, Katarina; et al. (Acta medicae Medianae, 2025)
Advances in technology and medicine have brought new solutions to challenges encountered in everyday practice. Since the implantation of the first epicardial pacemaker about half a century ago, the refinement and miniaturization process of the device has resulted in the latest generation of artificial heart guides (VVS), which, with the help of sophisticated technology, overcomes the obstacles of conventional devices. The Micra pacemaker is a single-chamber device that weighs 2 g, has a volume of 0.8 cm², and is capsule-shaped, measuring 25.9 mm in length and 6.7 mm in outer diameter. The size of the device not only does not limit the functions of the device but also represents a significant advantage and novelty in the world of implantable devices. This paper presents a series of the first 6 cases of transcatheter transvenous implantation of a miniature artificial heart guide Medtronic Micra (Medtronic, Minnesota, USA) device for permanent cardiac stimulation at the University Clinical Center Niš. The Micra system without electrodes has proven in practice to be a safe and effective option for permanent cardiac pacing in adult patients. In certain patients in whom the usual venous access is impossible (multiple sternotomies, thoractomies, congenital or acquired anomalies), it has become the most useful alternative in the case of indication for permanent pacing.
Keywords: Micra pacemaker, pacemaker implantation, complications